2000
DOI: 10.1111/j.1651-2227.2000.tb00423.x
|View full text |Cite
|
Sign up to set email alerts
|

Quality of life in childhood asthma: use of the Paediatric Asthma Quality of Life Questionnaire in a Swedish sample of children 7 to 9 years old

Abstract: Reichenberg K, Broberg AG. Quality of life in childhood asthma: use of the Paediatric Asthma Quality of Life Questionnaire in a Swedish sample of children 7 to 9 years old. Acta Paediatr 2000; 89: 989-95. Stockholm. ISSN 0803-5253To validate a Swedish translation of the Paediatric Asthma Quality of Life Questionnaire (PAQLQ) and to study determinants of asthmatic children's quality of life, seventy-one 7-9-y-old children and their families were approached. Sixty-one children (86%) participated, 36 boys and 25 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
43
1
5

Year Published

2003
2003
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 80 publications
(59 citation statements)
references
References 8 publications
10
43
1
5
Order By: Relevance
“…Surprisingly, a couple of studies indicate that food-induced breathing difficulties or asthma is a factor predicting 'not so bad' QoL in children; that is, better QoL than in children with asthma but no food allergy [38] and better QoL than in children with other adverse food reactions than breathing difficulties [29 ]. By contrast, food induced gastrointestinal symptoms seem to have a major negative impact on parents [29 ], adolescents and young adults [22,23 ,24 ].…”
Section: Food Hypersensitivity Quality Of Life and Comorbiditymentioning
confidence: 92%
“…Surprisingly, a couple of studies indicate that food-induced breathing difficulties or asthma is a factor predicting 'not so bad' QoL in children; that is, better QoL than in children with asthma but no food allergy [38] and better QoL than in children with other adverse food reactions than breathing difficulties [29 ]. By contrast, food induced gastrointestinal symptoms seem to have a major negative impact on parents [29 ], adolescents and young adults [22,23 ,24 ].…”
Section: Food Hypersensitivity Quality Of Life and Comorbiditymentioning
confidence: 92%
“…A PubMed database search (March of 2009) for PAQLQ validation studies rendered 13 articles, 8 of which were cultural validation studies. (19,(21)(22)(23)(24)(25)(26)(27) Of those, there were two different reports of the validation of the Spanish-language version and one regarding the independent Brazilian version previously mentioned. However, among those studies, diverse methodologies were used to assess the properties.…”
Section: Resultsmentioning
confidence: 99%
“…(23) In two other studies, only the convergent validity of the PAQLQ was reported (23,27) ; only one study evaluated floor/ceiling effects (23) ; and we were surprised to find that, in another study, no psychometric assessment was performed, the authors justifying that omission by stating that they had found scores similar to those reported in the original PAQLQ study, and that that would be sufficient to consider their validation appropriate. (22) In a validation study, the number of validity and reliability components included should be sufficient to provide an overview of its psychometric performance. (7) Correlations between the PAQLQ scores and FEV 1 were similar to what has previously been reported, (24)(25)(26) and the lack of strong correlations is no surprise.…”
Section: Resultsmentioning
confidence: 99%
“…Literatürle uyumlu olarak kız ve erkeklerde zorlanılan faaliyetlerde ilk sırayı koşma almaktadır (28 …”
Section: Discussionunclassified